Associations between TNFSF15 polymorphisms and susceptibility to ulcerative colitis and Crohn's disease: A meta-analysis. (December 2014) - Zhang, Jixiang; Zhang, Jihui; Wu, Dandan; Wang, Jun; Dong, Weiguo
Abstract Aims: Several polymorphisms have been identified in TNFSF15, while their roles in the incidence of ulcerative colitis (UC) and Crohn's disease (CD) are conflicting. This meta-analysis was aimed to clarify the impact of these polymorphisms on UC and CD risk. Method: Databases were searched until 31 January 2014 for eligible studies on TNFSF15 polymorphisms. Data were extracted, and pooled odd ratios (ORs) as well as 95% confidence intervals (95% CIs) were calculated. Results: Fifteen studies with 8903 CD patients, 4687 UC patients and 12 606 controls were included. Except for rs4263839 polymorphism, significant associations were found between the rest six TNFSF15 polymorphisms and CD risk (rs3810936: OR = 2.10, 95% CI, 1.47–3.00; rs6478108: OR = 2.19, 95% CI, 1.53–3.13; rs4979462: OR = 1.89, 95% CI, 1.42–2.52; rs6478109: OR = 2.00, 95% CI, 1.39–2.88; rs7848647: OR = 1.54, 95% CI, 1.15–2.06; rs7869487: OR = 1.51, 95% CI, 1.06–2.17). And we found rs3810936, rs6478108 and rs6478109 polymorphism were significantly associated with UC risk (rs3810936: OR = 1.19, 95% CI, 1.06–1.34; rs6478108: OR = 1.16, 95% CI, 1.06–1.26; rs6478109: OR = 1.16, 95% CI, 1.03–1.32). According to the subgroup analysis by ethnicity, except for rs4263839 in Caucasian and rs4979462 in Asian, all the rest investigated TNFSF15 polymorphisms were associated with CD risk and rs3810936 and rs7848647 polymorphism in Asian as well as rs6478108 polymorphism in Caucasian were associated with UC risk. Conclusion: This meta-analysis indicated that most of the seven TNFSF15 polymorphisms (except for rs4263839) were risk factors contributed to CD and UC susceptibility. The differences in ethnicity did not influence the risk obviously.